2019
DOI: 10.1007/s41669-019-0117-4
|View full text |Cite
|
Sign up to set email alerts
|

Economic Impact and Clinical Outcomes of Omalizumab Add-On Therapy for Patients with Severe Persistent Asthma: A Real-World Study

Abstract: Background Omalizumab is a fully humanized monoclonal antibody indicated as add-on therapy to improve asthma control in patients with severe persistent allergic asthma. Aims The aim of this study was to evaluate social, healthcare expenditure and clinical outcomes changes after incorporating omalizumab into standard treatment in the control of severe asthma. Methods In this multicentre retrospective study, a total of 220 patients were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 38 publications
(36 reference statements)
1
6
1
Order By: Relevance
“…25 Another evaluation of 220 patients from 15 pulmonology departments in Andalusia and Extremadura, also in Spain, found that the mean cost per patient was 12,690.00 EUR one year after starting complementary anti-IgE therapy; the cost-effectiveness per exacerbation avoided was 1712 EUR. 26 Although the average costs per patient are higher than those reported in our study, it is important to consider that patients in the Spanish cohorts had days of hospitalization and visits to the emergency room.…”
Section: Discussioncontrasting
confidence: 53%
“…25 Another evaluation of 220 patients from 15 pulmonology departments in Andalusia and Extremadura, also in Spain, found that the mean cost per patient was 12,690.00 EUR one year after starting complementary anti-IgE therapy; the cost-effectiveness per exacerbation avoided was 1712 EUR. 26 Although the average costs per patient are higher than those reported in our study, it is important to consider that patients in the Spanish cohorts had days of hospitalization and visits to the emergency room.…”
Section: Discussioncontrasting
confidence: 53%
“…After screening 1884 hits and reviewing 36 full text articles, 22 economic evaluations were included (Figure 2, Table ). Two studies evaluated benralizumab, one dupilumab and twenty studies omalizumab (Table ). Most of the studies excluded did not evaluate patients with allergic asthma (3/14), did not report health outcomes (3/14) or were conference abstracts (3/14) (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…We have no data in children for comparison, but in two studies in adult patients in our country, the ICER varied from €1488 to €1712 euros per avoided MSE with the same criteria we used. 29,30 When these studies included indirect costs, not available in our patients, the figures decreased to €1130 and €1607 euros, reductions of 24% and 6%, respectively. In two studies in adults, the figures per avoided exacerbation were €1789 and €2244 euros, including indirect costs.…”
Section: Ta B L Ementioning
confidence: 86%
“…In the first year of treatment of our patients the mean ICER to avoid an MSE (main objective of this report) was €2107 euros (median €998). We have no data in children for comparison, but in two studies in adult patients in our country, the ICER varied from €1488 to €1712 euros per avoided MSE with the same criteria we used 29,30 . When these studies included indirect costs, not available in our patients, the figures decreased to €1130 and €1607 euros, reductions of 24% and 6%, respectively.…”
Section: Discussionmentioning
confidence: 98%